IMPLEMENTASI SUPERVISI MANAJERIAL DALAM MENINGKATKAN MUTU SEKOLAH DI SMP NEGERI 8 BINJAI - Sari Andini; Nasrul Syakur Chaniago (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of managerial supervision in improving school quality at SMP Negeri 8 Binjai, covering aspects of planning, implementation, evaluation, follow-up, and the challenges encountered. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research informants consist of the principal, vice principal, teachers, and education staff selected through purposive sampling. The results of the study indicate that managerial supervision has been implemented through relatively systematic stages. In the planning stage, supervision is designed based on school needs and previous evaluation results by determining focus areas, schedules, and supervision instruments. In the implementation stage, supervision is carried out through monitoring, guidance, and collaborative discussions between supervisors and school stakeholders. In the evaluation stage, supervision is conducted through reflection and follow-up discussions; however, weaknesses were still found in the documentation aspect, which has not been optimally organized. The follow-up of supervision is carried out through administrative improvements, adjustment of work programs, and strengthening coordination among school components.